The city of stardust - Summers, Georgia (Redhook, 2024)
"For centuries, the Everlys have seen their best and brightest disappear, taken as punishment for a crime no one remembers, for a purpose no one understands. Their tormentor, a woman named Penelope, never ages, never grows sick - and never forgives a debt. Violet Everly was a child when her mother left on a stormy night, determined to break the curse. When Marianne never returns, Penelope issues an ultimatum: Violet has ten years to find her mother, or she will take her place. Violet is the last of the Everly line, the last to suffer. Unless she can break the curse first. Her hunt leads her into a seductive magical underworld of power-hungry scholars, fickle gods and monsters bent on revenge. And into the path of Penelope's quiet assistant, Aleksander, who she knows cannot be trusted - and yet to whom she finds herself undeniably drawn. With her time running out, Violet will travel the edges of the world to find Marianne and the key to the city of stardust, where the Everly story began."--